PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DI PT TRIO MOTOR HONDA WAREHOUSE BANJARMASIN - Mailiana Mailiana; Diana Hayati; Siti Rahayu (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research aims to examine the effect of work discipline on employee performance at PT Trio Motor Honda Warehouse Banjarmasin. Subjects in this study were as many as 40 people. According to Arikunto (1998; 120) that "If the subject is less than 100, better taken all, so the research is a population study." So the sample of this research amounted to 40 people. Collecting technique is done by means of data collection techniques used by the author in this study is by way of observation, questionnaires, interviews, documentation. The results of this research indicate that the results of simple linear regression test showed that the discipline variable has a significant influence on the performance of the employees of the Logistics Division at PT Trio Motor Honda Warehouse Banjarmasin with the probability value of 0.045 variable (smaller than 0.05) The regression coefficient shows a positive value of 0.178 which can be interpreted a positive influence between discipline on the performance of employees in the Division of Logistics PT Trio Motor Honda Warehouse Banjarmasin and based on the coefficient of determination showed that the discipline affect the performance of 10.4% .The remaining 89.6% influenced by other variables or other factors such as work motivation, compensation, and others.